The Auborus Formation of the Bethanie district, South West Africa - Miller, R McG (Department of Geological Sciences, 2016)
A study of the southerly occurrence of Auborus sediments revealed a basal conglomerate varying in thickness from 100 ft. to 3300 ft. and lying unconformably on an undulating base of lavas and sediments of the Sinclair Formation. This is overlain by variable thicknesses of sandstone which contain a few interbedded conglomerate bands, most of which are wedge-shaped. Intercalated grit is present in both the sandstone and the conglomerate zones. Shale occurs in the north-west where the sediments reach a thickness of 8500 ft. Nama sediments overlie the formation unconformably. Deposition, after rapid erosion and decay, took place under warm humid conditions into a shallow, slowly subsiding, intracratonic basin. Inward dipping edges were produced by contemporaneous subsidence. Vertical post-depositional movements in the central section folded the beds of the whole succession in the west into vertical and overturned positions. Block faulting that followed had a meridional trend and elevated this central section. Roughly north-trending faulting has displaced the contact in the south-east, and two later sets of east-west faults occur in the north-east. Diagonal, release and tension joints were revealed by measurement. Fracture planes in conglomerate pebbles apparently show no relationship to nearby faults. Pebble, cobble and boulder conglomerates contain a great variety of rock types, which have mostly been identified as coming from nearby southerly sources. A matrix is always present. The sandstone is a uniform red colour, very fine-grained, well sorted, very well compacted and is felspathic and arkosic in character. Rock fragments are ubiquitous. The colouring matter is intergranular, crystalline hematite. Felspars and biotite show various stages of alteration. A little recrystallization of quartz has taken place. The main heavy minerals are ore (largely specularite), garnet, epidote, zoisite, clinozoisite, mica, monazite, zircon and tourmaline. Zircon has been classified on colour, roundness, inclusions and zoning; tourmaline on colour, roundness and inclusions. Bedding in the sands tone is from thin to laminated. The commonest sedimentary structures are cross-beds, mud cracks and clay-pellet impressions. Other features are ripple marks, parting lineations, flute casts and rain prints. The red colour was probably produced in the source area. Diagenetic processes have produced spots of decoloration; and some joints show decoloration. Chemical analyses have been made of the red beds and a decolored spot.